Quantum Hairy Black Hole Formation and Horizon Quantum Mechanics - Cavalcanti, Rogerio Teixeira [UNESP]; da Silva, Julio Marny Hoff [UNESP] (MDPI, 2023)
After introducing the gravitational decoupling method and the hairy black hole recently derived from it, we investigate the formation of quantum hairy black holes by applying the horizon quantum mechanics formalism. It enables us to determine how external fields, characterized by hairy parameters, affect the probability of spherically symmetric black hole formation and the generalized uncertainty principle.
Keywords: generalized uncertainty principle; gravitational decoupling; hairy black holes; horizon quantum mechanics; quantum black holes